A nomogram for the prediction of cerebrovascular disease among patients with brain necrosis after radiotherapy for nasopharyngeal carcinoma. (March 2019) - Cai, Jinhua; Cheng, Jinping; Li, Honghong; Lin, Wei-Jye; Li, Yi; Zhuo, Xiaohuang; Huang, Xiaolong; Simone, Charles B.; Aronow, Wilbert S.; Chow, Edward L.W.; Tang, Yamei
Highlights: A nomogram to predict cerebrovascular disease in brain necrosis after radiotherapy. The nomogram shows favorable discrimination and calibration. The nomogram is capable to stratify patients into high- and low-risk groups. This reliable and easy-to-use predictive tool may aid in clinical decision making. Abstract: Background and purpose: This study sought to develop and validate a nomogram to predict cerebrovascular disease (CVD) among patients with brain necrosis after radiotherapy for nasopharyngeal carcinoma (NPC). Materials and methods: A total of 346 eligible patients with brain necrosis after radiotherapy for NPC were divided into a training set ( n  = 231) and a validation set ( n  = 115). A multivariate Cox proportional hazards regression model was used to select the significant variables for CVD prediction in the training set. Then, a nomogram was developed based on the regression model. The performance of the nomogram was assessed with respect to discrimination and calibration. All patients were classified into high- or low-risk groups based on the risk scores derived from the nomogram. Moreover, a decision curve analysis was performed with the combined training and validation sets to evaluate the clinical usefulness of the nomogram. Results: Four significant predictors were identified: hypertension, statin treatment, serum level of high-density lipoprotein, and interval between radiotherapy and brain necrosis. The nomogram incorporating these four predictors showed favorable calibration and discrimination regarding the training set, with a C-index of 0.763 (95% CI, 0.694 to 0.832), which was confirmed using the validation set (C-index 0.768; 95% CI, 0.675 to 0.861). Furthermore, the nomogram successfully stratified patients into high- and low-risk groups. The decision curve indicated that our nomogram was clinically useful. Conclusion: The nomogram showed favorable predictive accuracy for CVD among patients with brain necrosis after radiotherapy for NPC and might aid in clinical decision making.